The Role of Virtual Cystoscopy, after Multidetector Computed Tomography Imaging Reconstruction without the Use of Contrast Medium, in the Diagnosis and Evaluations of Bladder Tumors: Preliminary Study. (2nd April 2014) - Kalokairinou, Kyriaki; Ploumidis, Achilles; Kalogeropoulos, Theodoros; Vlachos, Lampros; Stringaris, Kyriakos; Tavernaraki, Ageliki; Thanos, Anastasios; Papacharalampous, Xenofon; Koutoulidis, Vasilios; Letendre, Julien; Traxer, Olivier; Gouliamos, Athanasios
Abstract : Introduction . Although conventional cystoscopy is considered to be the gold standard for diagnosis and follow-up of bladder tumors, it remains an invasive and costly procedure. With the advent of the multidetector CT (MDCT) scanners supported by specialized software virtual cystoscopy (VC) is possible. We assess the role of VC in diagnosing and evaluating bladder lesions. Materials and Methods . Between September 2010 and October 2011, 25 consecutive patients with cystoscopically confirmed bladder tumor underwent VC. The radiologists involved in this prospective study were blinded to the exact findings. After draining any residual urine with a catheter, the bladder was retrogradely insufflated with 200–600 cc of air. No intravenous or intravesical contrast was used. MDCT scan was performed in supine and prone positions and three-dimensional reconstruction of the urinary bladder was performed. Results . The examination was well tolerated by all patients with no complications. In total, 43 lesions were detected both with conventional cystoscopy and VC. Tumor size measured by CT ranged from 3 to 80 mm in diameter. The pathological report revealed noninvasive transitional cell carcinomas in all cases. Conclusion . VC has promising results in detecting exophytic bladder lesions. In the future it could be part of the diagnostic algorithm for bladder tumors.